Preparation and physicochemical properties of an injectable alginate-based hydrogel by the regulated release of divalent ions via the hydrolysis of d-glucono-δ-lactone. (February 2020) - Sun, Xiaojun; Li, Zhaoyang; Cui, Zhenduo; Wu, Shuilin; Zhu, Shengli; Liang, Yanqin; Yang, Xianjin
In this study, an injectable dopamine-modified alginate hydrogel combined with nano-hydroxyapatite or strontium hydroxyapatite was cross-linked via the in situ slow release of divalent ions from the hydrolysis of D-glucono-δ-lactone (GDL). The cross-linking mechanism involved the chelation of an alginate with divalent ions and the hydrogen-bonding interaction between alginate and catechol groups. As the GDL concentration at 0.5% (w/v) regulated the release of the divalent ions, which enhanced the chelation effect, it was investigated, and inorganic nanoparticles were homogeneously distributed into the hydrogel system to improve the mechanical properties and stabilize the hydrogel network. Furthermore, the effects of dopamine on the improvement of the mechanical properties were investigated. Results demonstrated that the compressive strength of this injectable hydrogel is enhanced by 4.6 times compared with that of the hydrogel without the addition of GDL, and the compressive strength is enhanced by 4.0 times compared with that of the unmodified alginate hydrogel at strain values ranging from 10% to 50%. The hydrogels combined with strontium hydroxyapatite exhibited a more compact, suitable pore size, with a three-dimensional network structure, and the particle size was 50–100 μm; this range of values is considered as optimal for the growth of bone tissues. In addition, the gelation time can be adjusted from a few minutes to a few seconds by adjusting experiment variables. Our study provides a potential method for improving the mechanical properties of bone tissue engineering materials. 1 HNMR, FTIR, and UV–vis spectroscopy measurements; XRD and SEM; and pH, ion release, and mechanical tests were carried out.